Crossroads of homocysteine, nitric oxide and asymmetric dimethylarginine metabolisms:involvement of S-adenosylhomocysteine and impaired cellular methylation - Rocha, Mónica Eunice dos Santos, 1979- (2012)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2012